Avaliação silvicultural de pau-de-balsa - Santin, Julio Cesar (2018)
The main goal was to evaluate the effect of fertilizer rates into different plant population on growth and production of balsa trees. This study started in January 2011 in Guarantã do Norte, North of Mato Grosso, Brazil with a 2x2 m, 3x2 m, and 3x3 m plant distribution treatments and four fertilizer rates treatments. The experimental design was randomized blocks with four replicates. There was a positive result of fertilizer doses with increases of almost 100% due to plant spacing and fertilizer doses. Commercial tree height was reached in the first year and was not affected by fertilizer application or plant spacing. The following soil chemical attributes changed in 2.2 years: pH, Al 3+, m (%), Ca, Mg, SB, and V (%), but the effect was observed only in the upper soil layer. Treatments with higher soil fertilizer quality (soil pH, SB and V (%) about 5.8 to 6.2, 5 cmolc dm-3 and 60% respectively) were also associated with a higher development of balsa plants.